Effect of the Rib Depth to the Overall Beam Depth Ratio in the Lightweight One-Way Ribbed Slabs - A. Abdulkareem, Taif; A. Alfeehan, Ashraf (International Journal of Engineering and Technology, 2018)
The ribbed slabs provide a lighter and stiffer slab than an equivalent traditional slab with minimizing the total volume of the materials. Four one-way lightweight concrete panels, including one flat and three ribbed panels were cast and tested under two-point load as simply supported up to the failure. The main investigated variable is a ratio of the rib depth (d) to the overall beam depth (h). All the panels have the same concrete volume and the same steel reinforcement ratio. Also, the width of the rib is equal to the slab thickness as a constraint condition in all the panels. Data were recorded at the loading stages to determine the load capacity and the deflection. A nonlinear finite element analysis carried out by using ANSYS-15 software program to analyze the panels and to verify the results. Increase the (d/h) ratio improved the structural behavior by increase the carrying load capacity and reduces the deflection to a certain limit. Compatibility results have been obtained between the numerical and experimental work.Â Â Â